Influence of solid nontransparent inclusion shape on the breakup time of heterogeneous water drops. (February 2019) - Antonov, D.V.; Vysokomornaya, O.V.; Piskunov, M.V.; Fedorenko, R.M.; Yan, W.M.
Abstract: The heat and mass transfer of evaporating heterogeneous water drops was numerically studied to determine the effects of internal solid non-transparent inclusions with different shapes on evaporation characteristics under intensive heating. Explosive breakup times of heterogeneous water drops were determined for various temperature of the gaseous environment with different solid inclusion shapes. Predicted results show that at 550 K, the minimum fragmentation time (~5.5 s) corresponded to the water drops with spherical inclusion as well as the maximum one (~9 s) was the water drops with ellipsoidal inclusion. At higher temperature (850 K), the minimum fragmentation time (~1.5 s) corresponded to the water drops with ellipsoid inclusion while the maximum time was for the water drops with sphere inclusion. Research results could be used for the development such technologies as fire extinguishing, surface treatment by heterogeneous flows, defrosting of granular media by high-temperature gas-vapor-drop flows, and thermal and flame water purification.